Early events in TCR signaling – the evolving role of ITAMs - Paul E. Love; Teri Hatzihristidis; Jayna Bryant; Guillaume Gaud (Frontiers in Immunology)
The T cell antigen receptor (TCR), a multiprotein complex essential for adaptive immunity, is composed of variable TCRα and TCRβ subunits responsible for antigen recognition and six invariant signal transducing CD3 and ζ subunits. Peptide-MHC (pMHC) binding by TCRα/β dimers results in the transmission of signals mediated by the CD3 and ζ subunits, which each contain one or more immunoreceptor tyrosine-based activation motifs (ITAMs). Several other immune receptors utilize ITAMs for signal transduction; however, while each of these receptors includes between one and three signaling subunits with a single ITAM, the TCR is strikingly unique, containing a total of ten ITAMs distributed within the six CD3 and ζ subunits. Numerous studies conducted over the past twenty-five years have attempted to determine the purpose for the structural singularity of the TCR. From these investigations, three models of ITAM function have emerged: signal discrimination (selective effector binding to different ITAMs), signal amplification (additive effect of ITAMs) and signal duality (activation and inhibition by ITAMs depending on context). In this review, we revisit the long history of ITAM research, which despite intensive investigation, has yet to provide a clear consensus for the role of TCR signaling subunit and ITAM multiplicity. We conclude by relating results from our recent study of the three tandem ζ ITAMs that suggest that at least some TCR ITAMs can transmit both activating (amplifying) and inhibitory signals depending on the affinity of the pMHC-TCR interaction and the subunit context, contributing to and enabling the nuanced regulation of T cell responses by the TCR and helping explain the exquisite ligand discrimination displayed by the TCR. These findings also suggest a model for ligand-mediated antagonism, a well-documented but poorly understood atypical TCR signaling response. Finally, we examine the implications of these findings which provide the basis for a new functional model for TCR ITAM multiplicity. A comprehensive understanding of the roles of ITAMs and the CD3 interactome will emerge from continued investigation, shedding light on the fascinating but still incompletely understood most proximal steps in the TCR signaling cascade.